Silas Enoch Burrows correspondence - Burrows, Silas Enoch, 1794-1870.
Correspondence between Burrows in Hong Kong and diplomat Karl Robert, Graf von Nesselrode.
Handwritten transcripts.
Merchant, shipowner, and world traveler.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Nesselrode, Karl Robert, -- Graf von, -- 1780-1862 -- Correspondence; Merchants -- Hong Kong; Merchants; Shipowners; Travelers